1990
DOI: 10.1084/jem.171.1.321
|View full text |Cite
|
Sign up to set email alerts
|

Functional analyses of thymic CD5+ B cells. Responsiveness to major histocompatibility complex class II-restricted T blasts but not to lipopolysaccharide or anti-IgM plus interleukin 4.

Abstract: In a previous report, we demonstrated that a small number of B cells are present in the thymus ofnormal mice, and that the majority ofthymic B cells show the phenotype observed for Ly-1 + (CD5 +) B cells in other tissues (1). Thus, the majority of thymic B cells express surface CD5, IgM, B220 (CD45R), and Mac-1(CDllb), and a lower amount of MHC class II relative to peripheral B cells. The functions of the CD5+ subset and the minor CD5-component in the thymus have not been determined, however, because of prior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 10 publications
2
20
0
Order By: Relevance
“…The number of B cells in the normal mouse thymus is approximately 0.1–0.3% of thymocytes, similar to the number of DCs or TECs (14, 15), and it has been reported that the majority of these B cells develop intra-thymically (11). The mechanisms supporting homeostasis of thymic B cells are not well understood.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…The number of B cells in the normal mouse thymus is approximately 0.1–0.3% of thymocytes, similar to the number of DCs or TECs (14, 15), and it has been reported that the majority of these B cells develop intra-thymically (11). The mechanisms supporting homeostasis of thymic B cells are not well understood.…”
Section: Introductionsupporting
confidence: 55%
“…The mechanisms supporting homeostasis of thymic B cells are not well understood. Previous studies have shown that T cell blasts support in vitro proliferation of thymic B cells (15), suggesting that T cell presence is important for the regulation of the thymic B cell population. This led us to hypothesize that there is a bidirectional interaction or cross-talk between thymic T cells and thymic B cells similar to that reported between T cells and mTECs (1620): that thymic B cells interact with T cells to mediate negative selection of autoreactive T cells, and thymic T cells in turn support maintenance of the thymic B cell population.…”
Section: Introductionmentioning
confidence: 99%
“…Further characterization in mice confirmed that these cells express a number of activation and costimulatory markers, such as CD5, CD69, CD80, CD86, CD40, and high levels of MHC class II [5, 25, 26]. Despite this activated phenotype, they displayed a reduced ability to proliferate and produce antibodies in response to classic B cell mitogens such as anti-IgM plus IL-4, and LPS relative to splenic B cells.…”
Section: Thymic B Cell Activationmentioning
confidence: 99%
“…It is hypothesized that select self antigens, which can be uniquely internalized by B cells, are processed and presented for the deletion of the appropriate T cell clones within the medulla and the thymic-cortical junction [24]. Functionally, thymic B cells have been shown to be different from splenic B cells since they proliferate relatively weakly in response to polyclonal B cell mitogens such as LPS or anti-IgM plus IL-4 [19]. In contrast, thymic B cells display strong proliferation and synthesis of Ig upon co-culture with appropriate peptide and MHCrestricted T cell clones and following CD40 ligation [25].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have been performed on the phenotypic characterization and biological function of thymic B cells [15][16][17][18][19]. These cells comprise <0.1% of total thymic cells [20] and have been shown to express MHC class II, sIgM, FcR, CD44, HSA, LFA-1 and CD40 which are cell surface markers also expressed by splenic B cells [21].…”
Section: Discussionmentioning
confidence: 99%